Psychological distress and resilience in patients with gastroenteropancreatic neuroendocrine tumor - Song, Lili; Cao, Yanshuo; Li, Jie; Lu, Ming; Tang, Lili (Frontiers in Endocrinology, 2022)
An increased incidence of gastroenteropancreatic neuroendocrine tumors (GEP-NETs) has been reported in many countries. However, the prevalence and impact factors of psychological distress and resilience in patients with GEP-NETs are unclear. We recruited 200 patients with GEP-NETs to assess psychological distress and resilience. Measures comprised the Distress Thermometer, the Hospital Anxiety and Depression Scale, Connor-Davidson Resilience scale and Medical Coping Modes Questionnaire. Our results found that the prevalence of distress, anxiety, depression and low resilience were 31.5%, 31%, 17.8%, and 25.9%, respectively. Female patients were more likely to be distressed, as were those with NET Grade 1, were partly aware of diagnosis, and had known the diagnosis less than 3 months. Distress positively correlated with acceptance-resignation, and resilience positively correlated with confrontation and avoidance. Resilience negatively correlated with psychological distress. Patients coping disease with acceptance-resignation had higher odds of anxiety, depression, and low resilience. Our findings indicate that psychological distress and low resilience were common in patients with GEP-NETs. This suggests a need to integrate psychosocial domain into GEP-NETs clinical practice.